Adult Play with Character Toys - Heljakka, Katriina (MDPI, 2026)
Character toys are toys identifiable by name, personality, and visual traits. They represent specific characters derived from or associated with popular culture. This entry explores adult engagement with character toys, or toy play, through a multidisciplinary lens, emphasizing playability, materiality, affect, creativity, and sociocultural meaning. Drawing on earlier toy research on dolls, action figures, figurines, and soft toys—those with a face and assigned personality—it considers how adults collect, customize, create stories, and critique societal conditions through toys for personal enrichment, identity work, and community formation. The toy play of adults is framed as a legitimate and complex form of self-expression and cultural participation that intersects with object play, creative fandoms, and political resistance.